2021
DOI: 10.26633/rpsp.2021.41
|View full text |Cite
|
Sign up to set email alerts
|

Embedding research into health services in Latin America and the Caribbean: experiences and challenges of the Technical Support Center

Abstract: This article describes the main models for embedding research and the successful experiences and challenges faced in joint work by researchers and decisionmakers who participated in the Embedding Research for the Sustainable Development Goals (ER-SDG) initiative, and the experience of the Technical Support Center. In June 2018, funding was granted to 13 pre-selected research projects from 11 middle- and low-income countries in Latin America and the Caribbean (Argentina, Bolivia, Brazil, Colombia, Dominican Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…32,33 Moving a step forward, as we discussed elsewhere, the best conditions for success can be linked to the presence of previous collaborations as well as the establishment of new relationships based on mutual trust. 34 As noted, it is hard to obtain evidence about the influence of the participation of research staff in the research process on the utilization of research results shortly after the finalisation of the research efforts. In fact, the literature rarely reports on decision-makers working in the design, execution and evaluation of research; unless its focus is precisely on these activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Moving a step forward, as we discussed elsewhere, the best conditions for success can be linked to the presence of previous collaborations as well as the establishment of new relationships based on mutual trust. 34 As noted, it is hard to obtain evidence about the influence of the participation of research staff in the research process on the utilization of research results shortly after the finalisation of the research efforts. In fact, the literature rarely reports on decision-makers working in the design, execution and evaluation of research; unless its focus is precisely on these activities.…”
Section: Discussionmentioning
confidence: 99%
“…Since the objectives as well as the research question are not posed by them, this may somehow limit effective action on real and perceived needs within health services, which not necessarily helps to strengthen health systems 32,33 . Moving a step forward, as we discussed elsewhere, the best conditions for success can be linked to the presence of previous collaborations as well as the establishment of new relationships based on mutual trust 34 …”
Section: Discussionmentioning
confidence: 99%
“…This sector also includes private insurance agencies called Prepaid Medicine Enterprises, nanced mostly through premiums paid by families and/or employers. 9 During 2019, a cross-sectional study was conducted in Argentina with the aim of characterizing the health-related quality of life (HRQOL) and economic impact in patients diagnosed with NSCLC who are treated in public hospitals, however, this study only had the perspective of patients served by the public health system and did not consider patients who are treated in the private healthcare sector. 10 Studies in other regions of the world have shown that the healthcare system or sector (private or public) is associated with differential nancial toxicity, so the estimate for the public sector may not be representative for the country as a whole, or for patients served by the private healthcare sector.…”
Section: Introductionmentioning
confidence: 99%